"Empathy without sympathy": An analysis of support-related preferences among young adult cancer survivors. Issue 4 (4th July 2022) - Darabos, Katie; Berger, Allison J.; Ford, Jennifer S.
Abstract: Objectives: Young adult cancer survivors often experience altered social relationships which may be a result of social support networks not knowing how to effectively provide the support young adults need. This study aimed to identify and describe themes of young adults' support preferences when engaging in cancer-related conversations and examine whether psychological distress is associated with support-related preferences. Methods: Young adult survivors ( M age =35.12, N  = 59) completed validated self-report measures of depression, cancer-related stress, social isolation, and two open-ended questions on types of preferred support. Results: Listening (81.4%) was most commonly preferred; showing pity/worry (33.9%) was most undesired. Other types of preferred support included empathy, validation, encouragement (42.4%), and honest conversation (23.7%); common types of undesirable support included being uninterested and changing the subject (32.3%), insensitive comments and questions (25.4%), and negative stories/personal comparisons (23.7%). Greater depressive symptoms (OR = 1.21, p  = .05) were associated with a preference for honest conversations whereas lower depressive symptoms (OR = 0.83, p  = 0.05) and greater cancer-related stress (OR = 1.07, p  = .02) were associated with a preference for conversations that did not contain advice. Lastly, lower perceived social isolation (OR = 0.88, p  = .05) was associated with a preference for conversations that were not minimizing and that did not contain expressions of pity/worry. Conclusions: Study findings can inform communication interventions and educate support networks about types of support young adults prefer when discussing cancer-related concerns.